Response surface methodology for optimisation of parameter on water absorption of natural fibre hybrid composite in boat construction - Mat Jusoh, Suriani; Zulkifli, Mohammad Fakhratul Ridwan; Abdullah, Samsuri; Shafi, Ayu Rafiqah; Mohd Nasir, Mohd Fadzhel; Maulana, Ummi Nurashira; Mohd Radzi, Fathin Sakinah; Zainulabidin, Syakir Hakimi (Universiti Putra Malaysia Press, 2024)
Today, the utilisation of natural or green fibre has supplanted engineered fibre as fibreglass has become a pattern in composite boat producing and other gears because of its lightweight, excellent relative mechanical properties, and more significant elements. For example, it is eco-accommodating, has manageable materials, and has lower costs compared to fibreglass. The utilisation of fibreglass is costly and has a high effect on the natural biological system. It also gets over the area of ecological contamination, word-related well-being, and security concerns. This study used the Woven Kenaf/fibreglass as reinforcement and polyester as matric to fabricate hybrid composite coupons. Response Surface Methodology (RSM) of Box-Behnken Design (BBD) was applied to optimise fibre contents (35 to 75 wt%) and water absorption performance for the development of Woven Kenaf/fibreglass to polyester hybrid composite material based on the parameters. The BBD revealed that 45% Woven Kenaf/fibreglass to polyester performed the optimum fibre content and water absorption. Analyses of variance (ANOVA) showed that the model satisfactorily correlated the parameters. After immersion, 45% Woven Kenaf/fibreglass to polyester composite also gained 9.48% weight.